1992
DOI: 10.1128/jcm.30.8.1958-1967.1992
|View full text |Cite
|
Sign up to set email alerts
|

Primary humoral antibody response to Coxiella burnetii, the causative agent of Q fever

Abstract: Of 147 patients with acute Q fever diagnosed during a major outbreak in Birmingham, England, in early summer 1989, 41 provided sets of sera which allowed us to make a detailed analysis of the primary humoral immune response. Antibody titers specific for CoxieUla burnetii were measured by the complement fixation test and by an immunoglobulin M (IgM)and IgG-specific indirect immunofluorescence test. The relative avidity of specific IgGs was determined by the indirect immunofluorescence test with and without trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…For example, Meurman et al, (1992) found that IgG antibody avidity in patients with respiratory syncytial virus infection can serve to distinguish between primary infection and reinfections. Secondary immune responses generate antibodies of higher avidity, Guigno et al, (1992) reported that IgG antibody avidity to Coxiella burnetii, the causative organism of Q fever, changed significantly when the time elapsed after infection is considered, Joynson et al, (1990) reported that patients with acute toxoplasmosis infection had low avidity IgG antibody while patients with chronic infection showed high avidity antibody. Consequently, analysis of antibody avidity to periodontal pathogens may help distinguish between acute exacerbations and quiescent periods of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Meurman et al, (1992) found that IgG antibody avidity in patients with respiratory syncytial virus infection can serve to distinguish between primary infection and reinfections. Secondary immune responses generate antibodies of higher avidity, Guigno et al, (1992) reported that IgG antibody avidity to Coxiella burnetii, the causative organism of Q fever, changed significantly when the time elapsed after infection is considered, Joynson et al, (1990) reported that patients with acute toxoplasmosis infection had low avidity IgG antibody while patients with chronic infection showed high avidity antibody. Consequently, analysis of antibody avidity to periodontal pathogens may help distinguish between acute exacerbations and quiescent periods of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-inactivated sera were tested against either phase I or phase II C. burnetii antigens (147). A complement fixation anti-phase II antibody titer of Ն40 indicated a diagnosis of acute Q fever (126), whereas an anti-phase I antibody titer of Ͼ200 indicated a diagnosis of chronic Q fever (273). The complement fixation test is specific but has a lower rate of sensitivity and is more time-consuming than IFA or ELISA (270).…”
Section: Serologymentioning
confidence: 99%
“…The complement fixation test is specific but has a lower rate of sensitivity and is more time-consuming than IFA or ELISA (270). Moreover, seroconversion is detected by complement fixation at a later date: 2 to 3 weeks for the complement fixation test, compared to 10 to 15 days for IFA and ELISA (126,270). In addition, false-negative results have been described with the complement fixation test in chronically infected patients with high antibody titers due to a prozone phenomenon, as well as false-positive results due to crossreactions with hen egg antigens.…”
Section: Serologymentioning
confidence: 99%
“…The interpretation of results requires acute-and convalescent-phase serum samples. Seroconversion is detected later by the complement fixation test than by the immunofluorescence assay or ELISA (between 10 and 20 days after the onset of symptoms) (57,134).…”
Section: Specific Laboratory Diagnosismentioning
confidence: 99%